Experimental Investigation of ZrCo Getter Beds as Candidate Process for the Tritium Extraction Systems of the European Test Blanket Modules. (19th May 2017) - Bükki-Deme, A.; Calderoni, P.; Demange, D.; Fanghänel, E.; Le, T.-L.; Sirch, M.; Ricapito, I.
Abstract: ZrCo is a well-known tritium storage material and has been studied intensively in the literature. The most interesting properties with regards to the thermodynamics of the ZrCo-H system are the very low H2 partial pressure in equilibrium with ZrCoH3 at room temperature and the ease to reach sufficiently high temperature to completely release the stored H2 . These properties motivate also to use ZrCo not as a simple storage, but rather as a concentrator of hydrogen isotopologues from inert gases like He. With such function, ZrCo getter beds are the reference solution adopted in the conceptual design of the tritium extraction system of the European Test Blanket Modules (TBM) to replace the cryogenic molecular sieve bed previously proposed. An experimental campaign was carried out on ZrCo in order to consolidate this choice. The results confirmed that ZrCo performs well as getter material but only substantially below the maximum loading capacity. They revealed that the dynamic thermo-mechanical response of the material, controlled by temperature and H2 concentration, is the main limiting factor for the component performance.